2016
DOI: 10.5812/aapm.39696
|View full text |Cite
|
Sign up to set email alerts
|

Cooled Radiofrequency Ablation of Genicular Nerves for Knee Osteoarthritis Pain: A Protocol for Patient Selection and Case Series

Abstract: BackgroundChronic knee pain from osteoarthritis (OA) is common in the aging and the obese population. Radiofrequency ablation of the genicular nerves has been introduced as a potential surgery-sparing treatment for chronic knee pain from OA, yet only two outcome studies have been published and optimal patient selection for this procedure has not been established.ObjectivesWe describe a standardized protocol for selecting patients for cooled radiofrequency ablation (C-RFA) of the genicular nerves, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 24 publications
0
27
0
Order By: Relevance
“…With the Medline and CEN-TRAL searches and review of references, a total of 17 studies were considered for this review. The degree of evidence regarding the efficacy of radiofrequency ablation in the literature was not substantially high -only 5 small-sized randomized controlled trials were identified with size ranging from 17 to 54 patients (6,8,(14)(15)(16). The remaining studies were retrospective (17)(18)(19)(20) and prospective (21)(22)(23)(24) observational case series and case reports (12,(25)(26)(27).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…With the Medline and CEN-TRAL searches and review of references, a total of 17 studies were considered for this review. The degree of evidence regarding the efficacy of radiofrequency ablation in the literature was not substantially high -only 5 small-sized randomized controlled trials were identified with size ranging from 17 to 54 patients (6,8,(14)(15)(16). The remaining studies were retrospective (17)(18)(19)(20) and prospective (21)(22)(23)(24) observational case series and case reports (12,(25)(26)(27).…”
Section: Methodsmentioning
confidence: 99%
“…Two studies (6,15) did not sufficiently specify the nerve target for RFA. In a randomized controlled trial of 54 patients, Shen et al (6) investigated RFA plus injection of platelet-rich plasma and sodium hyaluronate compared to injection alone. The authors described their approach as "we applied RFTC to the peripheral nerve of the knee joint."…”
Section: Nerve Targetsmentioning
confidence: 99%
See 3 more Smart Citations